2004
DOI: 10.33584/jnzg.2004.66.2542
|View full text |Cite
|
Sign up to set email alerts
|

Quality and quantity of chicory, lucerne and red clover production under irrigation

Abstract: The quality and quantity of production from irrigated lucerne, chicory and red clover swards were compared over six years (30 November 1996 30 June 2002) on a Wakanui silt loam at Lincoln University. Mean annual yields from lucerne swards (21 t DM/ha) were 3.9 t/ha greater than chicory and red clover over five perennial regrowth seasons. Sown species gave 100% of dry matter (DM) production in the first regrowth season, but by the fifth season sown species gave 65, 55 and 0% of DM production for chicory, lucern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
(16 reference statements)
3
12
0
Order By: Relevance
“…The slight increase in DMD contents of the plants in the final week of the trial was probably due to the filling of grain in the triticale and pod formation in the Hungarian vetch. The changes in nutritive quality parameters in the present study were in line with the results of Brown & Moot (2004), who reported that ME in the palatable fraction of the legumes generally remains constant as the plants grow and herbage is accumulated compared to cereal crops and grass species, which generally have dramatic reductions in their nutritive value with increasing DM production and development.…”
Section: Discussionsupporting
confidence: 92%
“…The slight increase in DMD contents of the plants in the final week of the trial was probably due to the filling of grain in the triticale and pod formation in the Hungarian vetch. The changes in nutritive quality parameters in the present study were in line with the results of Brown & Moot (2004), who reported that ME in the palatable fraction of the legumes generally remains constant as the plants grow and herbage is accumulated compared to cereal crops and grass species, which generally have dramatic reductions in their nutritive value with increasing DM production and development.…”
Section: Discussionsupporting
confidence: 92%
“…In 2004, Brown and Moot's study [ 85 ] established that combined herbage quality and greater herbage consumptions of lucerne forage afforded 30% greater annual crude protein (CP) and ME intake for sward than chicory or red clover. This indicates that lucerne has greater potential to improve livestock production.…”
Section: Chicory: Specialist Livestock Foragementioning
confidence: 99%
“…This reduced the overall quality of the feed on offer, through an allometric decline in the leaf to stem ratio (Lemarie, Sinclair, Sadras, & Bélanger, 2019; Ta et al, 2020). In practice, the animals can be expected to select the leaf and the soft stem components of the lucerne (Brown & Moot, 2004), so liveweight gains and the nutritive value of the ingested feed can be higher than the feed on offer. However, a delayed start of spring grazing frequently leads to higher crop residuals of lucerne (Moot et al., 2016) as the hard, lignified stem is avoided, which was apparent in the lower leaf to stem ratio of T500 crops.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the potential benefits for grazing lucerne, several recent studies have investigated the mechanisms responsible for the relationships between herbage mass and quality ( e.g. Brown & Moot, 2004; Ta, Teixeira, Brown, & Moot, 2020; Lemaire & Bélanger, 2020), seasonal changes in remobilization and partitioning of assimilates (Brown, Moot, & Teixeira, 2006; Khaity & Lemaire, 1992) and drivers of crop growth and development (Teixeira, Brown, Meenken, & Moot, 2011). Collectively, these studies have allowed development of grazing management rules independent of phenological state ( i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation